Experimental analysis of the thermohygrometric effects on the dynamic behavior of adobe systems. (30th May 2019) - Zonno, Giacomo; Aguilar, Rafael; Boroschek, Rubén; Lourenço, Paulo B.
Highlights: Structural and environmental continuous monitoring of adobe masonry was carried out. Internal hygrometric measurements was not influenced by external conditions. Environmental seasonal and daily effects were isolated from the structural response. Daily results show a delayed effect of the env. conditions in structural response. Results indicate a clear inverse relationship of temperature and dynamic properties. Abstract: Through long-term monitoring, modal parameters identified in-situ can provide important information about the safety state of civil buildings and infrastructures. Unfortunately, structures are subjected to changing environmental conditions that can mask variations in the dynamic properties caused by damage and, therefore, lead to an incorrect condition assessment. The quantification of the influence of environmental conditions on modal parameters is a crucial step to eliminate their interference in a safety evaluation. Under current state-of-the-art considerations, this step is still an open challenge because environmental variables are time-dependent non-uniform quantities that have different influences on structural systems depending on the predominant material. In this paper, the effects of ambient temperature and humidity on the dynamic properties of earthen constructions are investigated using laboratory tests. A dynamic monitoring system was successfully implemented on adobe walls of different thicknesses to examine the influence of seasonal and daily variations of temperature and humidity. Three 1:1 scale adobe masonry walls were built and exposed to ambient conditions for 240 days. Temperature and humidity variations on the exterior, as well as in the inner walls, were continuously recorded together with the dynamic behavior using ambient vibration. The results provide useful insights on the influence of thermohygrometric parameters on the dynamic properties of adobe systems. The seasonal results indicate unclear correlations of ambient parameters and environmental variables. On the other hand, at a daily scale, the results indicate the existence of a clear relationship between inner measurements and dynamic properties. Moreover, the results indicate the existence of a delayed effect of external ambient parameters in the dynamic behavior of earthen systems.